2017
DOI: 10.3390/ijms18102096
|View full text |Cite
|
Sign up to set email alerts
|

Spot-Bonding and Full-Bonding Techniques for Fiber Reinforced Composite (FRC) and Metallic Retainers

Abstract: Fiber reinforced Composite (FRC) retainers have been introduced as an aesthetic alternative to conventional metallic splints, but present high rigidity. The purpose of the present investigation was to evaluate bending and fracture loads of FRC splints bonded with conventional full-coverage of the FRC with a composite compared with an experimental bonding technique with a partial (spot-) resin composite cover. Stainless steel rectangular flat, stainless steel round, and FRC retainers were tested at 0.2 and 0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…The null hypothesis of the present investigation was rejected: significant differences were reported among various groups. In this report, three different materials, which are used in orthodontic splints, were tested for different times of tooth brushing: stainless steel, FRC covered with a composite (used in the FRC covered conventional technique), and non-covered FRC (used in the experimental uncovered spot-bonding FRC technique) [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The null hypothesis of the present investigation was rejected: significant differences were reported among various groups. In this report, three different materials, which are used in orthodontic splints, were tested for different times of tooth brushing: stainless steel, FRC covered with a composite (used in the FRC covered conventional technique), and non-covered FRC (used in the experimental uncovered spot-bonding FRC technique) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of the present report is based on previous studies that demonstrated that FRC retainers have a higher rigidity if compared to metal splints and that this feature is less desirable. Previous studies also demonstrated that retainers made of FRCs without composite coverage have values of rigidity more similar to values of metal retainers, and this is a positive feature [21,22,24,25]. Finally brushing interferes with all restorative materials previously tested changing their mechanical properties [27].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Several studies investigated the most used retention device in various European and non-European countries, and bonded retainers resulted to be the most widely used device in different countries, especially for the mandibular arch [3][4][5][6][7][8]. This is due to their reliability, independence of patient compliance, high effectiveness, simplicity of application, almost invisibility ( Figure 1) and well acceptance by patients [9]. In restorative dentistry, it is believed that considerable benefits are obtained from etching enamel with phosphoric acid prior to the application of a universal adhesive system: the results of various studies show, indeed, that the bonding force (shear bond strength) of these adhesives increases considerably following pre-etching of the enamel [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%